Central Auditory Processing Dysfunction in Service Members and Veterans: Treatment Considerations and Strategies. - Tepe, Victoria; Guillory, Lisa; Boudin-George, Amy; Cantelmo, Tasha; Murphy, Sara (Journal of Speech, Language & Hearing Research, 2023)
Purpose: Military risk factors such as blast exposure, noise exposure, head trauma, and neurotoxin exposure place Service members and Veterans at risk for deficits associated with auditory processing dysfunction. However, there is no clinical guidance specific to the treatment of auditory processing deficits in this unique population. We provide an overview of available treatments and their limited supporting evidence for use in adults, emphasizing the need for multidisciplinary case management and interdisciplinary research to support evidence-based solutions. Method: We explored relevant literature to inform the treatment of auditory processing dysfunction in adults, with emphasis on findings involving active or former military personnel. We were able to identify a limited number of studies, pertaining primarily to the treatment of auditory processing deficits through the use of assistive technologies and training strategies. We assessed the current state of the science for knowledge gaps that warrant additional study. Conclusions: Auditory processing deficits often co-occur with other military injuries and may pose significant risk in military operational and occupational settings. Research is needed to advance clinical diagnostic and rehabilitative capabilities, guide treatment planning, support effective multidisciplinary management, and inform fitness-for-duty standards. We emphasize the need for an inclusive approach to the assessment and treatment of auditory processing concerns in Service members and Veterans and for evidence-based solutions to address complex military risk factors and injuries.